2021
DOI: 10.1029/2021jc017767
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Transport of the South Atlantic Subtropical Mode Water in Eddy‐Permitting Observations

Abstract: The spatio-temporal variability of such heat and CO 2 uptake and storage is dependent on various physical mechanisms from both ocean surface and subsurface perspectives. Intuitively, air-sea heat and momentum fluxes generate and modulate sea surface temperature (SST) anomalies, which in turn, provide feedback to these fluxes (Park et al., 2005). In addition, studies have also observed and examined a reemergence mechanism of SST anomalies from one winter to another, without maintaining through the summer in bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 83 publications
2
13
0
Order By: Relevance
“…Our Type I MW relates to the most saline variety (SASTMW2), and the Type II MW to the densest variety (SASTMW3). Corroborating the conclusions of ; Chen et al (2022) demonstrated that, contrary to the findings of Smythe-Wright et al (1996), a ring in the southeast Atlantic carrying MW with a potential temperature of 13°C and salinity of 35.2 psu originated at the Agulhas Retroflection and not at the Brazil-Malvinas Confluence as initially supposed, corroborating the conclusions of . Whether the 12-13°C thermostad, by origin, is subantarctic or subtropical, from a remote site in the South Indian Ocean, or locally formed, remains controversial and deserves more research.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Our Type I MW relates to the most saline variety (SASTMW2), and the Type II MW to the densest variety (SASTMW3). Corroborating the conclusions of ; Chen et al (2022) demonstrated that, contrary to the findings of Smythe-Wright et al (1996), a ring in the southeast Atlantic carrying MW with a potential temperature of 13°C and salinity of 35.2 psu originated at the Agulhas Retroflection and not at the Brazil-Malvinas Confluence as initially supposed, corroborating the conclusions of . Whether the 12-13°C thermostad, by origin, is subantarctic or subtropical, from a remote site in the South Indian Ocean, or locally formed, remains controversial and deserves more research.…”
Section: Discussionsupporting
confidence: 74%
“…Using numerical modeling, Capuano et al (2018) demonstrated the role of turbulence and instabilities in the Cape Basin on the transformation of water masses from the Indian Ocean and subduction of MW inside Agulhas rings. Using a new algorithm to detect MW in Argo profiles, including outcropping MW, Chen et al (2022) suggested a new interpretation of the origin and formation of the MWs found in the upper thermocline of the South Atlantic Ocean. Their results led to a redefinition of the three types of South Atlantic STMW, where the origins of both the lightest and the densest varieties were found mainly inside the southeastern Cape Basin, related to the Agulhas Leakage, while Sato and Polito (2014) argued that two varieties are related to the Brazil-Malvinas Confluence.…”
Section: Introductionmentioning
confidence: 99%
“…A winter with strong heat loss is expected to deepen MLD a lot, including inside-eddy, and a subsequently warmer winter could then not achieve to deepen the MLD as much. This mechanism drives mode-water formation, and it was already shown in other regions, mostly the Atlantic Ocean, that eddies could modulate mode-water formation (Dugan et al, 1982;Chen et al, 2022). Such hypothesis could also explain the high occurrence of 'non-connecting' events in the Mediterranean sea, this region being known for a high interannual variability of winter heat loss.…”
Section: Double-core Eddy Formationmentioning
confidence: 77%
“…2c; Table 1). South Atlantic Central Waters (SACW) are produced locally as they originate from the subduction of subtropical Mode Waters in hotspots of air-sea interaction and eddy activity in the southwestern Atlantic at the Brazil-Malvinas Confluence (BMC) and the southeastern Atlantic 127,128 (Box 1). These two regional hotspots also encompass pathways whereby relatively fresh and highly oxygenated intermediate waters enter the South Atlantic.…”
Section: Box 1 | Observing the Overturning Circulation In The South A...mentioning
confidence: 99%
“…Despite its small area, upper ocean warming in the South Atlantic accounts for roughly 10% of global upper ocean warming. Some of this excess heat has been taken up by subtropical Atlantic mode waters since nearly 1980, which then ventilate the main thermocline and transport heat away from the surface 128,138,148,149 . South Atlantic AAIW properties also show significant warming, and their salinity seems to be decreasing over the past few decades 148,150 (Fig.…”
Section: Box 1 | Observing the Overturning Circulation In The South A...mentioning
confidence: 99%